Ammonia regulation of amino acid permeases in Saccharomyces cerevisiae. - Courchesne, W E (1983)
The activities of the proline-specific permease (PUT4) and the general amino acid permease (GAP1) of Saccharomyces cerevisiae vary 70- to 140-fold in response to the nitrogen source of the growth medium. The PUT4 and GAP1 permease activities are regulated by control of synthesis and control of activity. These permeases are irreversibly inactivated by addition of ammonia or glutamine, lowering the activity to that found during steady-state growth on these nitrogen sources. Mutants altered in the regulation of the PUT4 permease (Per-) have been isolated. The mutations in these strains are pleiotropic and affect many other permeases, but have no direct effect on various cytoplasmic enzymes involved in nitrogen assimilation. In strains having one class of mutations (per1), ammonia inactivation of the PUT4 and GAP1 permeases did not occur, whereas glutamate and glutamine inactivation did. Thus, there appear to be two independent inactivation systems, one responding to ammonia and one responding to glutamate (or a metabolite of glutamate). The mutations were found to be nuclear and recessive. The inactivation systems are constitutive and do not require transport of the effector molecules per se, apparently operating on the inside of the cytoplasmic membrane. The ammonia inactivation was found not to require a functional glutamate dehydrogenase (NADP). These mutants were used to show that ammonia exerts control of arginase synthesis largely by inducer exclusion. This may be the primary mode of nitrogen regulation for most nitrogen-regulated enzymes of S. cerevisiae.